Bisogna difendere la società. La questione dell’identità razziale tra Michel Foucault ed Étienne Balibar (Altre Modernità, 2017)
Faced with the growth of nationalism and racism in Occident, this essay aims to provide some theoretical tools to think ‘historically’ racism. To this end, I propose a study of the reflections of Foucault and Balibar about this issue. Their positions, although different, converge in approaching racism  as a problem connected with the construction of identity, in which the stakes are, according to Balibar, the political hegemony of a class in the national context, and, according to Foucault, the establishment of power relationships in the social context. In the years in which Foucault studies the genesis of racism, he’s also interested to the political role of knowledge as tool both of domination and struggle. So, according to his re-enacting, biological racism takes form in opposition to the idea of revolution to present the domination of a part of society as something founded in their dangerous nature.  Balibar assumes that after the decolonization a new racism has taken shape, in which the category of race has been replaced by that of immigration. According to the new racism, cultures can’t live in peace if they mix each other and the only antidote to racism is closing nation’s borders. In this regard, Balibar shows that the same creation of nation needs the division of society in races: racism appears so closely connected with nationalism but also with ideology of class, that presents differences of class as insuperable anthropological and moral differences.